الهيدروجين: طاقة متجددة لتخفيض انبعاثات غاز ثاني أكسيد الكربون – الواقع والآفاق-: Hydrogen: a Renewabel Energy to Reduce Carbon Dioxide Emissions –Reality and Prospects- - بولقرينات سليمة (Journal of North African Economies, 2025)
This study aims to show the reality and prospects for using clean hydrogen to reduce carbon dioxide emissions. The descriptive and analytical approach was relied upon to accurately describe the variables of the study, as well as the analysis of the global use of clean hydrogen, as well as the analysis of its situation in a group of countries, including Algeria. The concept of carbon dioxide emissions was discussed, as well as study of the concept of renewable energies and its most important sources, including hydrogen energy and its types, the Status of hydrogen energy in the world was also studied, with a focus on low-carbon hydrogen, its was concluded and investment for hydrogen is in a countinuous increase until the horizons of 2050, and that most countries of the world have concluded several alliances regarding the exploitation of hydrogen energy, especially since the costs of low-carbon hydrogen are constantly declining until the horizons of 2050.